PENGARUH PENGULANGAN PENCELUPAN TERHADAP HASIL WARNA BAHAN SUTERA DENGAN EKSTRAK BATANG PISANG KEPOK (Musa paradisiaca L.cv kepok) - Zulmi, Yuliya; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aims to reveal the color (hue), dark-light color (value), the flatness of color and light and dark color difference (value) and flatness of color. This study was an experimental study. This type of data is a primary data sourced from 15 panelists. The object is a silk cloth dipped with kepok banana’s bark extract with repetition dyeing. Where the data analysis was performed using one-way ANOVA technique and Percentage. Result of the repetition of 5 times to produce color dyeing French Grey 30% with light and dark colors (value) is in the category of very bright and flatness of color are in the category of very flat. At 10 times the repetition dyeing produce color French Grey 50% with light and dark colors (value) is quite bright and flat colors flatness. And for the immersion repetition 15 times to produce color French Grey 70% with light and dark colors (value) is quite bright and flat colors flatness. The result of research by testing with results of hypothesis shows that light and dark colors (value) with F count (28.488) > F table (0.514). Result of research for flatness of the color showed differences in the flatness of color with F count (14.175) > F table (0.514), then Ho is rejected meaning that there are significant differences. Keywords: Repetition dyeing, the color, kepok’s banana bark extract